2015
DOI: 10.4103/0973-1482.136023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oxitard capsules in the treatment of oral submucous fibrosis

Abstract: Though there is no definitive treatment for the condition; however, oxitard capsules can bring about significant clinical improvements in the symptoms like mouth-opening, tongue protrusion, burning sensation, difficulty in swallowing and speech and pain associated with the lesion, thereby improving the quality of life of the affected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Various studies are stated in literature with significant mean improvement in mouth opening using levamisole (2.9 mm), micronutrients (2.9 mm), antoxid (3.1 mm), intralesional hydrocortisone with hyaluronidase and lycopene (3.4 mm and 5.38 mm), pentoxifylline with garlic pearls (5 mm), turmeric with tulsi (3-4 mm), turmeric with black pepper (3.8 mm), and intralesional dexamethasone with placental extract (3.5 mm) which is in favor of our study while studies published using intralesional INF-gamma (8 mm) and oxitard (12 mm) have shown better results. [7,13,14,[20][21][22][23][24][25][26][27][28] The present study with isometric exercises is in consonance with the studies published on micronutrients with isometric exercises (3.1 mm), tongue blade (3.1 mm), and ultrasound (3.74 mm) and better results were shown in dynasplint (7 mm) and Therabite (10 mm). [21,[29][30][31] The mean increment in tongue protrusion and cheek flexibility was 2.4 mm and 0.7 mm, respectively, which was comparable with topical Aloe vera gel, turmeric and black pepper, Nigella sativa, and pentoxifylline together.…”
Section: Discussionsupporting
confidence: 84%
“…Various studies are stated in literature with significant mean improvement in mouth opening using levamisole (2.9 mm), micronutrients (2.9 mm), antoxid (3.1 mm), intralesional hydrocortisone with hyaluronidase and lycopene (3.4 mm and 5.38 mm), pentoxifylline with garlic pearls (5 mm), turmeric with tulsi (3-4 mm), turmeric with black pepper (3.8 mm), and intralesional dexamethasone with placental extract (3.5 mm) which is in favor of our study while studies published using intralesional INF-gamma (8 mm) and oxitard (12 mm) have shown better results. [7,13,14,[20][21][22][23][24][25][26][27][28] The present study with isometric exercises is in consonance with the studies published on micronutrients with isometric exercises (3.1 mm), tongue blade (3.1 mm), and ultrasound (3.74 mm) and better results were shown in dynasplint (7 mm) and Therabite (10 mm). [21,[29][30][31] The mean increment in tongue protrusion and cheek flexibility was 2.4 mm and 0.7 mm, respectively, which was comparable with topical Aloe vera gel, turmeric and black pepper, Nigella sativa, and pentoxifylline together.…”
Section: Discussionsupporting
confidence: 84%
“…Chemopreventive Effects of Nutrient Antioxidants as a Potential OSMF Treatment A total of 26 clinical studies and one dual study [8] supported the chemoprotective role of antioxidant supplementation. Clinical improvements in at least one OSMF symptom (mouth opening, mucosal burning sensation, tongue protrusion, cheek flexibility, difficulty in swallowing and speech, pain associated with the lesion, oral health-related quality of life) were observed after administration of lycopene [57][58][59][60][61][62][63][64][65], alpha-lipoic acid [66], allicin [67], rebamipide [68], pentoxifylline [69,70], oxitard [59,71,72], aloe vera [71,[73][74][75][76][77], curcumin [77][78][79][80][81], and spirulina [75,82] (Table 2).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…When compared to standard antioxidant capsules, aloe vera produced greater improvements in burning sensation and mouth opening [74], while pentoxifylline showed further reduction in dysphagia and burning sensation [69]. Aloe vera was less effective in improving mouth opening when compared to spirulina [75], and also less effective in improving swallowing, speech, and pain associated with the lesion when compared with oxitard capsules [71]. However, when compared to curcumin, aloe vera brought larger improvements in burning sensation, but the two were equally effective in increasing mouth opening [77].…”
Section: Chemopreventive Effects Of Nutrient Antioxidants As An Effic...mentioning
confidence: 99%
“…OSMF presents clinically as blanching of the oral mucosa, burning sensation, ulceration, pain, decreased mobility and depapillation of the tongue, depigmentation of the oral mucosa, and progressive reduction of mouth opening. Severe cases of OSMF presents with nasal twang due and difficulty in hearing [5,6].…”
Section: Introductionmentioning
confidence: 99%